Mental health is the most important factor influencing quality of life in elderly left behind when families migrate out of rural China - Jian-fei Xie; Si-qing Ding; Zhu-qing Zhong; Qi-feng Yi; Sai-nan Zeng; Jun-hua Hu; Jian-da Zhou (Universidade de São Paulo, 2014)
OBJECTIVES: to investigate the quality of life and the associated factors on left behind elderly in rural China.METHOD: the research was conducted cluster sampling to select 456 elderly left behind when family members migrated out of rural China to participate in a cross-sectional study by completing a general data questionnaire and Quality of Life questionnaire.RESULTS: 91.5% of the elderly requested psychological counseling and education. For the elderly, scores for mental health (39.56±13.73) were significantly lower compared with Chinese standard data (61.6±13.7) (P<0.001). Age, chronic disease type, gender, residence pattern and economic support from children were the main psychological factors influencing this population.CONCLUSION: mental health is the most important factor influencing quality of life of elderly left behind when family members migrated out of rural China. Our study suggested a need to widely establish a general practitioner team for psychological intervention for improving rural elderly people's Quality of Life level, especially in the psychological domain.